2013
DOI: 10.5194/angeo-31-305-2013
|View full text |Cite
|
Sign up to set email alerts
|

Characterising electron butterfly pitch angle distributions in the magnetosphere through observations and simulations

Abstract: The Imaging Electron Spectrometer (IES) on the Polar satellite has measured the average characteristics of the equatorial electron pitch angle distributions (PADs) in the midnight sector as a function of radial distance out to the 9 <I>R</I><sub>E</sub> apogee of the Polar satellite. Depressions in the observed fluxes of electrons occur with pitch angles around 90° in the equatorial zone, while the more field-aligned electrons remain largely unchanged. The orbital precessions of the sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…The minimum flux at α ∼ 90 ∘ is well seen. In contrast to some previous observations [e.g., Fritz et al , ; Klida and Fritz , , ], the butterfly pitch angle distribution is formed only for high energies, while for energies <1 MeV, the pancake pitch angle distribution is not modified during the entire time interval. A weak minima of fluxes of high‐energy equatorial (with α ∼ 90 ∘ ) electrons shown in Figure e is likely related to the beginning of the formation of the butterfly pitch angle distribution.…”
Section: Observationscontrasting
confidence: 94%
See 1 more Smart Citation
“…The minimum flux at α ∼ 90 ∘ is well seen. In contrast to some previous observations [e.g., Fritz et al , ; Klida and Fritz , , ], the butterfly pitch angle distribution is formed only for high energies, while for energies <1 MeV, the pancake pitch angle distribution is not modified during the entire time interval. A weak minima of fluxes of high‐energy equatorial (with α ∼ 90 ∘ ) electrons shown in Figure e is likely related to the beginning of the formation of the butterfly pitch angle distribution.…”
Section: Observationscontrasting
confidence: 94%
“…Further, the survey of ISEE‐1 observations supported the idea of the formation of butterfly pitch angle distributions over a wide energy range (20 keV–2 MeV) due to splitting of drift shells and magnetopause shadowing [ Fritz et al , ]. Similar results were obtained using the Polar observations of electron pitch angle distributions [ Klida and Fritz , , ]. However, Gannon et al [] demonstrated the dominance of electron butterfly distributions in the nightside and higher L shells for energies larger than 500 keV.…”
Section: Introductionmentioning
confidence: 64%
“…This shows that the consequence of large jumps in J for particles with small initial values of J, is net transport away from α0 = 90°. Butterfly PADs are observed throughout the night‐time sector (West et al., 1973) and have been identified as deriving from drift shell splitting combined with magnetopause shadowing (e.g., Klida & Fritz, 2013), interactions with ULF waves (e.g., Kamiya et al., 2018) and particle injections (e.g., Artemyev et al., 2015). Here, we identify DOBs as a mechanism that might also produce such a distribution.…”
Section: Test‐particle Simulationsmentioning
confidence: 99%
“…Butterfly distributions have been attributed to the effects of shell splitting or magnetopause shadowing as electrons drift [ West et al ., ; Klida and Fritz , ]. Considering the longer time scale of electrons drifting over one orbit, however, this effect should be less important during dipolarization.…”
Section: Summary and Discussionmentioning
confidence: 99%